The atypical Rac activator Dock180 (Dock1) regulates myoblast fusion in vivo - Laurin, Mélanie (National Academy of Sciences, 2008)
Dock1 (also known as Dock180) is a prototypical member of a new family of atypical Rho GTPase activators. Genetic studies in Drosophila and Caenorhabditis elegans have demonstrated that Dock1 orthologues in these organisms have a crucial role in activating Rac GTPase signaling. We generated mutant alleles of the closely related Dock1 and Dock5 genes to study their function in mammals. We report that while Dock5 is dispensable for normal mouse embryogenesis, Dock1 has an essential role in embryonic development. A dramatic reduction of all skeletal muscle tissues is observed in Dock1-null embryos. Mechanistically, this embryonic defect is attributed to a strong deficiency in myoblast fusion, which is detectable both in vitro and in vivo. Furthermore, we have uncovered a contribution of Dock5 toward myofiber development. These studies identify Dock1 and Dock5 as critical regulators of the fusion step during primary myogenesis in mammals and demonstrate that a specific component of the myoblast fusion machinery identified in Drosophila plays an evolutionarily conserved role in higher vertebrates.